Analysis of Financial Performance Development Based on Profitability Ratios - Prasetya, Hendra; Evianah, Evianah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
A company's financial performance can be a factor considered by investors planning to invest. Financial statements serve as an important tool to evaluate a company's ability to generate profits, manage assets, and provide returns to shareholders. Therefore, financial performance analysis is needed to provide an overview of the company's health condition as well as the prospects for its business sustainability. The objective of this study was to evaluate the financial performance of PT Indofood CBP Sukses Makmur Tbk. for the 2022-2024 period using profitability indicators, namely Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results of the analysis indicate a positive trend, reflecting consistent improvement in the company’s profitability over the three-year period. This is reflected in the NPM, ROA, and ROE values, which continued to increase from 2022-2024, although the increase decreased from 2023 to 2024 compared to the increase from 2022-2023. From 2022-2024, the NPM values were 9.36%; 11.57%; and 11.57%, respectively and 11.87%. ROA values were 5.26%, 6.59%, and 6.84%. ROE values were 10.55%, 12.65%, and 12.86%. It is recommended that the company implement efficiency measures to increase profits. Although the rate of increase experienced a slowdown in 2024, overall the company was able to improve the effectiveness of asset and capital management as well as increase the ability to generate profit. By implementing efficiency and strengthening operational strategy, the company has the potential to maintain or even improve its financial performance in the following period.